Soil–water characteristic curves of Singapore residual soils - Agus, Setianto Samingan (2011)
Soil–water characteristic curves were obtained for a number of Singapore residual soil samples. Soil samples were obtained from the two main residual soil formations, the Jurong sedimentary formation and the Bukit Timah granitic formation, at various depths. The effect of weathering on the shape of the soil–water characteristic curve is examined. As the test procedure in obtaining the soil–water characteristic curve is tedious and time-consuming, empirical relationships based on multivariate analysis relating the parameters of the Fredlund and Xing (1994) soil–water characteristic curve equation to basic soil properties are suggested for the Singapore residual soils. The multivariate equations were found to be suitable for providing a quick preliminary estimate of the soil–water characteristic curve of Singapore residual soils.